Extrapolation of explicit DIMSIMs of high order to solve the ordinary differential equations - Annie a/p Gorgey (Tanjong Malim, 2019)
Extrapolation of explicit DIMSIMs of high order to solve the ordinary differential equations by Annie a/p Gorgey